THE ROLE OF COMPANY SIZE AS A MODERATING VARIABLE ON COMPANY VALUE IN INFRASTRUCTURE COMPANIES ON THE IDX - Diana Dwi Astuti; Nurshadrina Kartika Sari; Septi Fatwa F (LPPM Institut Teknologi dan Sains Mandala, 2025)
This research aims to analyze the influence of capital structure, liquidity and profitability on company value in Infrastructure Sector Companies listed on the BEI for the 2019-2023 period and to analyze the influence of capital structure, liquidity and profitability on company value in Infrastructure Sector Companies listed on the BEI 2019-2023 period with company size as a moderating variable. The population used in this research is Infrastructure Sector Companies registered on the BEI. The analysis techniques used in this research are classical assumption testing, hypothesis testing, and moderated regression analysis (MRA). The research results show that capital structure has an effect on company value, while liquidity and profitability have no effect on company value. The results of the moderation analysis show that company size can moderate the influence of capital structure, while company size cannot moderate the influence of liquidity and profitability on company value.